KONTRIBUSI MOTIVASI BERPRESTASI DAN KONSEP DIRI TERHADAP KETAHANMALANGAN (ADVERSITY QUATION) PADA MAHASISWA S1 PENDIDIKAN SENI DRAMA, TARI DAN MUSIK IKIP PGRI BALI - Bawa, Pande Wayan; Juliawan, I Wayan (Widyadari : Jurnal Pendidikan, 2019)
The purpose of this study was (1) Knowing the Contribution of Motivation to Achievement to the Resilience of students of S1 Drama, Dance and Music Arts Education Study Program IKIP PGRI BALI. (2) Knowing the contribution of self-concept to the resilience of students of S1 Drama, Dance and Music Arts Education Study Program IKIP PGRI BALI. (3) Knowing the Motivation Contribution of Achievement and self-concept to the resilience of students of S1 Drama, Dance and Music Arts Education Study Program IKIP PGRI BALI. The method used is correlational multiple regression through exposure facto (exposure to facts) with the implementation stage as follows, First, taking Motivation data Achieving student achievement through questionnaire dissemination. Then the self concept data collection that is owned by students is done by distributing questionnaires. The next stage is the data retrieval of Resilience through questionnaires and observations. The final stage is analyzing the results data with multiple regression methods. The targeted output is (a) Information about student Achievement and Self-Concept Motivation, (b). Information about students' resilience, (c) Scientific articles that are ready to be published in the Journal. The results of the study show that (1) there is a contribution to Achievement Motivation towards the durability of S1 graduate students with a value of rcount (0.70)> rtable (0.138) at a significance level of 0.05 of 0.138, (2) there is a significant contribution of self-concept to the resilience of S1 Bachelor degree students with a value of rcount (0.80)> rtable (0.138) at the 0.05 level of significance, (3) there is a contribution of Motivation Achievement and self-concept towards the resilience of students in the Bachelor of Medical Sciences with Fc 1560.05> 3, 04 or Fcount> Ftable at the 0.05 level of significance. From the findings above, it can be concluded that Resilience is influenced by Achievement Motivation and self-concept of students.